Reviews of Environmental Contamination and Toxicology - Whitacre, David M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
CONTENTS Foreword Preface The Fate of Arsenic in Soil-Plant Systems Eduardo Moreno-Jiménez, Elvira Esteban, and Jesús M. Peñalosa Evaluating the Toxicity of Selected Types of Nanochemicals Vineet Kumar, Avnesh Kumari, Praveen Guleria and Sudesh Kumar Yadav Adsorption and Desorption of Chlorpyrifos to Soils and Sediments Seyoum Yami Gebremariam, Marc W. Beutel, David R. Yonge, Markus Flury, and James B. Harsh Index.
Foreword -- Preface -- The Fate of Arsenic in Soil-Plant Systems -- Evaluating the Toxicity of Selected Types of Nanochemicals -- Adsorption and Desorption of Chlorpyrifos to Soils and Sediments -- Index.
Keywords: Ecotoxicology; Environmental management; Waste management; Ecotoxicology; Environmental Management; Waste Management/Waste Technology